Probing questions and feedback for learners with down syndrome in an inclusive classroom - Astuty; Farikah; Mursia Ekawati (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to investigate the practice of Assessment for Learning (AfL) in the context of inclusive classes focused on how teachers provide effective probing questions and feedback to Down Syndrome (DS) learners. This study involved two teachers from two inclusive elementary schools. The data was collected during the learning process and interviews with teachers and DS students. This research conducted qualitative research used on this study is descriptive qualitative that utters the teachers by using three considerations in providing effective probing questions and feedback for DS students. Those considerations are (1) the level of intelligence by giving direct, short, concrete questions; (2) social-emotional by giving feedback and reinforcement; and (3) limitations of other mental functions by using visual media and non-verbal language. The implications of this study show that the presence of learners with special needs is as important as normal children in an inclusive class. Thus, the teacher must be able to design the learning practice with the diversity of students. The training can be given to them as well. Along with that, the finding of this study can contribute to it. By giving them training, the teacher's confidence, and positive attitude toward teaching in the inclusive class are built up.